2023
DOI: 10.3389/fmicb.2023.869907
|View full text |Cite
|
Sign up to set email alerts
|

Vertical organization of microbial communities in Salineta hypersaline wetland, Spain

Abstract: Microbial communities inhabiting hypersaline wetlands, well adapted to the environmental fluctuations due to flooding and desiccation events, play a key role in the biogeochemical cycles, ensuring ecosystem service. To better understand the ecosystem functioning, we studied soil microbial communities of Salineta wetland (NE Spain) in dry and wet seasons in three different landscape stations representing situations characteristic of ephemeral saline lakes: S1 soil usually submerged, S2 soil intermittently flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…In the last years, LDA/PERMANOVA analysis has been used as a robust method to integrate multiple variables to evaluate associations in many biological, ecological, and environmental data sets [ 40 , 41 ]. In ECG data analysis, the use of univariate statistics was unable to identify significant differences in any of these parameters, hence, multivariate analysis had a greater power to identify statistical changes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, LDA/PERMANOVA analysis has been used as a robust method to integrate multiple variables to evaluate associations in many biological, ecological, and environmental data sets [ 40 , 41 ]. In ECG data analysis, the use of univariate statistics was unable to identify significant differences in any of these parameters, hence, multivariate analysis had a greater power to identify statistical changes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil bacterial taxa (genera) of apples that differed significantly in terms of relative abundance in mono- and intercropped systems were identified as potential biomarkers by the linear discriminant analysis (LDA) effect size (LEfSe) analysis. 1 Taxa were identified at genus level using the following parameters: (1) α-value = 0.05 for factorial Kruskal-Wallis tests among classes and (2) threshold logarithmic LDA score > 2.0 for differential features ( Bourhane et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the UAE in particular many wetlands, have been irretrievably lost, affecting the country's biodiversity [82]. It has been reported that biomonitoring and good management of hypersaline wetlands with extreme aridity and salinity is essential, especially in dealing with irreversible changes due to human activity [83]. In the UAE, climate change is expected to increase temperatures and salin-ity [84].…”
Section: Management Of the Reservementioning
confidence: 99%